(3ELGRGJ (B- (3eLehYIs - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s
(3ChdgG (B:s
(3Chd GdELGRI GdChdi , bhdg (B: (3CeG HYO , adeG cGf Ydi cd TjN ELGRI GdQhGjI , def jYJeO Ydjg ef JdGePJg hcGf KeQI aDGOi hdOfG eMeO GHf YHO GdhgGH GdgeOGfi eSJLjRkG efi Pdc , hSGdckG ef GdYde CMSf GdeSGdc s
(3BNQgG (B:s
(3BNQ GdELGRI GdQGHYI , bhdg (B: (3hefgG ELGRI gjcd GdWdHI eMeO Jbi Hf MSjf Ydi GdgQhi hai JGQjN MjGRJg dELGRGJ GdYdeGA GdCaGVd hJaQOg HgG ef Hjf GdCbQGf GdCeGKd , jbhd GdbGFd heP CLGRhg HENJHGQ RGO Hg CQN EaJNGQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B/ (3GdfLa (B(1745/1) s
Keywords: (3GdJGQjNs